Acute and Subchronic Toxicity Assessment of Proteins from Plumeria pudica Latex in Mice (Research, Society and Development, 2021)
Latex proteins extracted from Plumeria pudica (LPPp) have anti-inflammatory activity in different experimental models. Considering this relevant result, we evaluated the toxicological aspects of the treatment of mice with LPPp. Acute and subchronic toxicities were determined by daily intraperitoneal administration of 40 mg/kg of LPPp for 10 or 20 days, respectively, and were followed by behavioral, hematological, biochemical and histopathological evaluation. Results showed no significant changes in body weight and organs of animals treated with LPPp. Total and differential blood leukocyte counts of LPPp groups did not differ from controls. There was no significant difference in aspartate aminotransferase, alanine aminotransferase, creatinine and urea measurements for the group treated for 20 days. The level of glutathione in the kidney was significantly higher in animals treated with LPPp in the acute toxicity test, but no differences were observed for the subchronic evaluation. The concentration of malondialdehyde and myeloperoxidase activity in the organs did not differ from controls. Histopathological examination of kidney, spleen and liver tissue of animals treated with LPPp revealed normal structures or reversible alterations. Intraperitoneal LD50 of LPPp was higher than 2,000 mg/kg. The data obtained reveal that LPPp is nontoxic at 40 mg/kg.